Chance and circumstance : twenty years with Cage and Cunningham - Brown, Carolyn, 1927- (Alfred A. Knopf, 2007)
This long-awaited memoir is an intimate chronicle of a crucial era in modern dance: the story of Brown's own remarkable career, of the formative years of the Merce Cunningham Dance Company, and of the two brilliant, iconoclastic, and forward-thinking artists at its center--Merce Cunningham and John Cage. From its inception in the 1950s until her departure in the 1970s, Brown was a major dancer in the company and part of the vibrant artistic community of downtown New York. She describes the exhilaration--and dire financial straits--of the company's early days, when composer Cage was musical director and Robert Rauschenberg designed lighting, sets and costumes; and the struggle for acceptance of their controversial, avant-garde dance. She explores Cunningham's technique, choreography, and experimentation with compositional procedures influenced by Cage. And she probes the personalities of these two men: the reticent, moody, often secretive Cunningham, and the effusive, fun-loving, enthusiastic Cage.--From publisher description.